FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KESIAPAN IBU MENGHADAPI MENOPAUSE DI WILAYAH KERJA PUSKESMAS GUGUK PANJANG - Sari, Novi Wulan; Yuniliza, Yuniliza (Menara Ilmu, 2020)
Based on data from Health Office of Bukittinggi (2018), there were 9,806 women at 45-59 years old throughout Bukittinggi. The highest number of premenopausal women at 4855 years old is in Guguk Panjang Community Health Center. They were 65 people. This study aimed to determine Some Factors Related to Mother's Readiness to Face Menopause in Guguk Panjang Community Health Center 2019. This study used descriptive analytical method (quantitative approach) with cross sectional study design. It was conducted on February 2019. The populations were premenopausal women in Guguk Panjang Health Center. Total sampling technique had been chosen as the samples. They were 65 respondents were chosen as the samples. The data were collected through interview by using questionnaire. Then, it was analyzed by Chi-Square statistical test and logistic regression with a confidence level of 95%. The results of this study showed that 33 respondents (50.8%) were ready to face menopause. Moreover, the results of statistical tests obtained that there was a correlation between knowledge (p= 0.023), attitude (p= 0.006) and family support (p= 0.002) toward mothers’ readiness in facing menopause in Guguk Panjang Community Health Cente in 2019. In short, the three factors in this study had a significant relationship with readiness to face menopause. Therefore, it is important for premenopausal mothers to add insight and is expected to be more active in participating in health counseling specifically about menopause. Keyword : Mother's Readiness Facing Menopause, Knowledge, Attitudes, and Family Support